Identifying values and preferences around the choice of analgesia for patients with acute trauma pain in emergency and prehospital settings: using group concept mapping methodology - Robin Christensen; Eva Ejlersen Wæhrens; Marianne Uggen Rasmussen; Kristina Tomra Nielsen; Anders Foehrby Overgaard; Louise Klokker (BMJ Open)
Objectives The main study aim was to examine the applicability of a novel method to assess the criterion of values and preferences within the Grading of Recommendation, Assessment, Development and Evaluation evidence to decision framework. The group concept mapping (GCM) approach was applied to identify, organise and prioritise values and preferences in the example of health professionals’ choice of analgesia for patients with acute trauma pain.Setting Prehospital and emergency care centres in the Nordic countries of Denmark, Norway, Sweden, Finland and Iceland.Participants Acute care health professionals with qualifications to administer analgesic agents to patients in emergency and prehospital settings, including advanced ambulance assistants, rescue officers, paramedics, emergency physicians and emergency nurses, participated in an online survey in which statements were generated (n=40) and structured (n=11) and finally analysed and interpreted in a validation meeting (n=4).Results Using GCM, ideas were generated and structured through online participation. Results were interpreted at a validation meeting. In total, 111 unique ideas were identified and organised into seven clusters: drug profile, administration, context, health professionals’ preferences and logistics, safety profile, patient’s medical history and acute clinical situation.Conclusions Based on GCM, a conceptual model was developed, and values and preferences around choice of analgesia in emergency care were revealed. Health professionals within acute care can apply the conceptual model to support their decision-making when choosing the best available treatment for pain for their patients in emergency care.